2021
DOI: 10.3390/antiox10050709
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Cinnamic Aldehyde Antioxidant Response Activating nanoParticles (ARAPas) for Vascular Applications

Abstract: Selective delivery of nuclear factor erythroid 2-related factor 2 (Nrf2) activators to the injured vasculature at the time of vascular surgical intervention has the potential to attenuate oxidative stress and decrease vascular smooth muscle cell (VSMC) hyperproliferation and migration towards the inner vessel wall. To this end, we developed a nanoformulation of cinnamic aldehyde (CA), termed Antioxidant Response Activating nanoParticles (ARAPas), that can be readily loaded into macrophages ex vivo. The CA-ARAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…71 Cartaya et al encapsulated CA into poly(lactic- co -glycolic acid)-poly(siloxane) pluronic micelles using a direct dissolution method to prepare antioxidant response-activated nanospheres, providing complete drug integrity protection and selective targeting of cells, effectively inhibiting the proliferation and migration of vascular smooth muscle cells. 72 CA-loaded micelles significantly increased the content of GSH compared to free unformulated CA. Raffai et al reported that CA-loaded micelles were synthesized by the Michael addition reaction.…”
Section: Novel Delivery Systems For Cinnamaldehydementioning
confidence: 88%
“…71 Cartaya et al encapsulated CA into poly(lactic- co -glycolic acid)-poly(siloxane) pluronic micelles using a direct dissolution method to prepare antioxidant response-activated nanospheres, providing complete drug integrity protection and selective targeting of cells, effectively inhibiting the proliferation and migration of vascular smooth muscle cells. 72 CA-loaded micelles significantly increased the content of GSH compared to free unformulated CA. Raffai et al reported that CA-loaded micelles were synthesized by the Michael addition reaction.…”
Section: Novel Delivery Systems For Cinnamaldehydementioning
confidence: 88%
“…The expression of Nrf2 in rodent models of primary or secondary PH is decreased [130]. The selective delivery of Nrf2 activators to the injured vasculature has the potential to attenuate oxidative stress and decrease VSMC hyper-proliferation and migration towards the inner vessel wall [131]. Nrf2 gene transfer or Nrf2-inducing drugs such as sulforaphane, epigallocatechin gallate, cinnamic aldehyde, and exendin-4 have shown therapeutic applications in vascular diseases [132][133][134][135][136].…”
Section: Nrf2 and Smooth Muscle Cell Phenotypic Switching In Media Re...mentioning
confidence: 99%
“…The migration and proliferation of smooth muscle cells in arterial media is an important link in the progression of atherosclerosis. During vascular surgical intervention, selective delivery of Nrf2 activator to injured blood vessels can reduce oxidative stress, reduce excessive proliferation of vascular smooth muscle cells (VSMC) and migration to the inner wall of blood vessels [30]. The proliferation and migration of smooth muscle cells undergo phenotypic transfer and become a synthetic type, which is conducive to lipid absorption and myogenic foam cells formation.…”
Section: Potential Relationship Of Nrf2/are Signaling Pathway In Peri...mentioning
confidence: 99%